An agriculture ministry addresses AIDS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A senior staff-member from the AIDS Control Unit of the Kenyan Ministry of Agriculture and Livestock Development, discusses how agriculture, and agricultural departments, need to adapt to meet the challenge of HIV/AIDS.